Kombinuotųjų stogo konstrukcijų lenkiamojo strypo racionalus projektavimas - Juozapaitis, Algirdas (Journal of Civil Engineering and Management, 1996)
Rational design of flexural rod in combined roof structuresThe paper discusses a calculation of rational parameters of main flexural rod used in combined roof structures. Geometrical non-linearity can be discussed separately when the member is subjected either to tension or compression. It has been established that rational parameters for rods subjected to compression-bending or tension-bending have to be determined from the non-linear analysis calculation of the parameters using the slender- ness parameter, i.e. when kl ≤ 1.Also combined roof structures with a non-continuous main member are discussed. The rational parameters were calculated from the geometrically non-linear analysis. Numerical testing has shown that the non-continuous main members of the combined structures are more effective than the continuous ones.Article in Lithuanian.First Published Online: 26 Jul 2012